Seed analysis as a means of identifying micronutrient deficiencies of Phaseolus vulgaris L. in the tropics - Brodrick, SJ; Amijee, F; Kipe-Nolt, Judith A.; Giller, Kenneth E. (1995)
Seed analysis can indicate differences in micronutrient availability between soils. Comparison of Phaseolus vulgaris L. with published analytical data indicated that the micronutrients most limiting for N2-fixation and growth in parts of East and soLithem Africa were Mo and Cu. Significant differences in seed Mo concentration occurred between neighbouring (arms. Less variation was found for Zn and Cu. Zinc and Cu in seed were inversely related to seed size and correlated with N, while Mo showed a significant inverse relationship to Zn and N but no relationship with seed size. A fivefold difference in Mo content occurred between two genotypes of similar seed size grown on the same fertile soil. Mean Mo content in the seeds of nine genotypes from a Mo-poor soil was 0.6 ig Mo seed and on a Mo-rich soil 6.4 ig Mo seed-1. None of the genotypes was a consistently good accumulator of micronutrients at aU sites, and soil type was the major cause of differences between the sites. Sowing seeds of sufficient Mo content on a Mo-poor soil prevented the production of Mo-deficient seeds until the fourth consecutive harvest on the same site.